An Example of Language Teacher – Science Teacher Cooperation For The Creation of Online Educational Resources in University Context - Elena PETREA; Antoanela PATRAS (Communications of International Proceedings, 2023)
Our article presents the context and the results of an interdisciplinary workshop held in Iasi University of Life Sciences, a workshop which aimed to impart practical knowledge, encourage collaborative working and foster professional links between participants – language teachers and science teachers who worked on the creation of online learning resources for students. Unlike general foreign language program, the creation of specialized language/language for specific purposes/language for professional purposes/ program involves the teacher-designer dealing with new contexts, which he/she is discovering and with which he/she must become familiar. A foreign language teacher in a life sciences university such as ours benefits from ongoing exchanges with teachers of scientific disciplines. On the one hand, the workshop presented in our article helped learners improve their specialized language skills for studying or participating in a scientific discipline or science content area. On the other hand, the activity described provided teachers with online shared work methods, methodological and technical expertise in the creation, production and mediation of multimedia courses. Teamwork involved individual teacher research, resource sharing and online collaboration to create learning materials using information and communication technologies. The course sequences created, on the biochemical constituents of human food, were integrated into a Moodle course module for students in the agri-food sector.
Keywords: E-learning modules; language for specific purposes; science teacher; agri-food industry students